Efficacy of Ginger in Preventing Postoperative Nausea and Vomiting: A Systematic Review and Meta‐Analysis. Issue 6 (26th July 2021) - Zhu, Wei; Dai, Yan; Huang, Mingjun; Li, Jiping
Abstract: Purpose: We aimed to synthesize the published evidence to evaluate the preventive efficacy of ginger on postoperative nausea and vomiting (PONV). Design: A systematic review and meta‐analysis were conducted in this study. Methods: PubMed, EMBASE, Cochrane Library, and CINAHL were systematically searched from their outset to October 2020, without language limitation. Randomized controlled trials (RCTs) comparing the effects of ginger and prophylactic antiemetics or placebo on PONV were included. Data were analyzed by the fixed effects model or random effects models regarding the results of heterogeneity. Findings: A total of 14 studies involving 1417 participants were included. Compared with placebo, the ginger group had significantly lower nausea severity (MD = −0.71, 95% CI = −1.37 to −0.06, p = 0.03) and lower proportion of rescue antiemetic use (RR = 0.71, 95% CI = 0.62–0.82, p < 0.001; RR = 0.71, 95% CI = 0.56–0.91, p < 0.001). The ginger group had significantly lower incidence of nausea and vomiting over 6 h after operation (RR = 0.68, 95% CI = 0.55–0.85, p < 0.001; RR = 0.78, 95% CI = 0.42–1.44, p = 0.43) compared with placebo. When compared with the prophylactic antiemetic group, the ginger group had significantly lower incidence of nausea (RR = 0.75, 95% CI = 0.56–0.99, p = 0.04), but no significant differences in the incidence of vomiting and proportion of rescue antiemetic use were found. Conclusions: Ginger was effective for the prevention of PONV. More RCTs comparing ginger and other prophylactic antiemetics are needed to evaluate whether ginger could replace the traditional prophylactic antiemetics. Clinical Relevance: This study's results could be used as an evidence for all patients following surgery who are at risk of PONV without allergy to ginger.